186 Exploration of diabetes & cardiovascular risks factors among oil sector workers in kuwait: 2013 pme & comparisons to the population. (24th April 2018) - Hasan, Mohammad
Abstract : Background: High levels of diabetes and associated cardiovascular risk factors have been reported in Kuwait. While there is limited research on prevalence and risk factors in the general population, the associations of diabetes with cardiovascular (CVD) disease risk factors among oil industry employees have not yet been extensively explored. This aim of this study was to establish prevalence of diabetes and associations between diabetes and CVD risk factors broken down by gender and ethnicity. Methods: A cross-sectional study of 7000 employees of a major oil company (corresponding to 94% of the total population of employees) was conducted. 18.1% were female and 26.8% were non-Kuwaiti nationals. Clinical (blood samples) and non-clinical data (e.g. weight, height, and medically diagnosed chronic conditions) were gathered upon their visit to a clinic and medical laboratory. Results: Prevalence of obesity (using BMI) in the sample was 33.3%. 35.8% were physically active. The prevalence of diabetes was 15.6%, of dyslipidemia 47.9% and of hypertension 14.8%. Advancing age (≥40 years), male gender, obesity, physical activity, high triglycerides, hypertension and were significantly associated with increased risk of diabetes in a multivariate analysis. Ethnicity also played a role. Conclusion: This study shows that among the cardiovascular disease risk factors reported by oil sector employees in Kuwait, apart from age; hypertension is of particular importance as a predictor of diabetes, especially for women. Health behaviours (e.g. smoking and physical activity) did not show expected or consistent multivariate associations with diabetes, across gender and nationality.